1. А) (a+3)(a-7)-2a(3a+5) = а^2 - 7а + 3а - 21 - 6а^2 - 10а = -5а^2 -14а - 21
Б) 4b(b-2)+(b-4)² = 4b^2 - 8b + b^2 - 8b + 16 = 5b^2 - 16b + 16
В) 3(y+2)²-91 = 3 (y^2 + 4y + 4) - 91 = 3y^2 + 12 y + 12 - 91 = 3y^2 + 12 y - 79
2. a) c³-16c = c (c^2 - 16) = c (c-4)(c+4)
b) 3a²-6a+2a² = 5a^2 - 6a = a (5a-6)
3. (3x-x²)²-x²(x+2(x-2)+2x(7+3x³) = 9x^2 - 6x^3 + x^4 - x^2 (x^2 - 4 + 14x + 6x^4) = 9x^2 - 6x^3 + x^4 - x^4 + 4x^2 - 14x^3 - 6x^6 = 13x^2 - 20x^3 - 6x^6
4. a) 16a⁴ - 1 = (4a^2 - 1) (4a^2 + 1) = (2a - 1) (2a + 1) (4a^2 + 1)
b) a-a²+b+b² = (a + b) - (a^2 - b^2) = (a + b) - (a + b) (a - b) = (a + b) (1 - a + b)
3/(2^(2 - x²) -1)² - 4/(2^(2- x²) -1) + 1 ≥ 0 ;
замена : t = 2^(2-x²) -1
3 / t² - 4 / t +1 ≥ 0 ;
(t² - 4t +3) / t² ≥ 0
для квадратного трехчлена t² - 4t +3 t₁=1 корень: 1² - 4*1+3 = 1- 4+3 =0.
t₂ =3/t₁=3/1=1 (или t₂ =4 -1=3)
* * * наконец можно и решить уравнение t² - 4t +3=0 * * *
(t² - 4t +3) / t² ≥ 0 ⇔ (t -1)(t - 3) / t² ≥ 0 .
+ + - +
Объяснение:a)
{ 2^(2-x²) -1 ≤ 1 ; 2^(2-x²) -1 ≠ 0 .⇔ { 2^(2-x²) ≤ 2 ; 2^(2-x²) ≠ 1 . ⇔
{ 2^(2-x²) ≤ 2¹ ; 2^(2-x²) ≠ 2⁰.⇔ {2-x² ≤ 1 ; 2 - x² ≠ 0.⇔{ x² -1 ≥ 0 ; x² ≠ 2⇔
{ (x+1)(x-1) ≥ 0 ; x ≠ ±√2 . ⇒ x∈ ( -∞ ; -√2 ) ∪ (-√2 ; -1] ∪ [1 ; √2) U (√2 ; ∞) .
b)
2^(2-x²) -1 ≥ 3 ⇔ 2^(2-x²) ≥ 4 ⇔2^(2-x²) ≥ 2² ⇔2- x² ≥ 2 ⇔ x² ≤ 0 ⇒ x=0.
ответ: x∈ ( -∞ ; -√2 ) ∪ (-√2 ; -1] ∪ { 0} ∪ [1 ; √2) U (√2 ; ∞) .